2014
DOI: 10.1097/gme.0000000000000093
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone dose-response relationships in hysterectomized women with or without oophorectomy

Abstract: Objective To determine dose-dependent effects of testosterone on sexual function, body composition, muscle performance, and physical function in hysterectomized women with and without oophorectomy. Methods 71 menopausal women who previously underwent hysterectomy with or without oophorectomy with total testosterone<31ng/dl or free testosterone<3.5 pg/ml received a standardized transdermal estradiol regimen during the 12-week run-in period, and were then randomized to receive weekly IM injections of placebo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 50 publications
1
53
1
Order By: Relevance
“…Huang et al reported dose-related increases in lean body mass and improvement in strength [32] in postmenopausal women with low gender-adjusted testosterone suggesting the potential for testosterone to improve body composition and physical function in women. Their results were supported by data from another recent study showing that muscle protein synthesis in postmenopausal women is actually stimulated by testosterone and progesterone but not by estradiol [33].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al reported dose-related increases in lean body mass and improvement in strength [32] in postmenopausal women with low gender-adjusted testosterone suggesting the potential for testosterone to improve body composition and physical function in women. Their results were supported by data from another recent study showing that muscle protein synthesis in postmenopausal women is actually stimulated by testosterone and progesterone but not by estradiol [33].…”
Section: Discussionmentioning
confidence: 99%
“…The sparsity of research investigations on the effects of exogenous testosterone on the physical performance of women probably reflects the ethical concerns about potential adverse effects. In one study on postmenopausal women, administration of different doses of testosterone (reaching a maximal mean circulating level of 7.3 nmol/L) for 24 weeks resulted in dose-dependent increases in mean muscle mass by as much as 4.4% and in muscle strength by 12-26% (54).…”
Section: Exogenous Androgens and Physical Performance In Womenmentioning
confidence: 99%
“…A black box warning was recently added to testosterone products marketed to men after a longitudinal study suggested a 30% higher risk of adverse cardiovascular outcomes (75), although this study has been criticized due to methodology concerns (76-79), and whether it is generalizable to women is unknown. Finally, it appears supraphysiological serum testosterone levels may be necessary to yield any benefit on sexual desire and arousal (80, 81). The use of compounded testosterone products for transdermal use is on the rise, but these products are not regulated and amount of testosterone in the product can be highly inconsistent (82).…”
Section: Treatments For Female Sexual Dysfunctionmentioning
confidence: 99%